Distal Intestinal Obstruction Syndrome in Patients with Cystic Fibrosis: Two Separate Cases in the Pediatric Intensive Care Unit - Merve Mısırlıoğlu; Ahmet Sezer; Dinçer Yıldızdaş; Özden Özgür Horoz; Faruk Ekinci; Selcan Türker Çolak; Dilek Özcan (Galenos Yayinevi, 2023)
Distal intestinal obstruction syndrome (DIOS), also defined as the equivalent of meconium ileus, is a sign of complete or partial ileocecal obstruction with intestinal contents in patients with cystic fibrosis. DIOS may occur because of darkened intestinal secretions, pancreatic insufficiency, undigested food residues and sticky stool stasis. Patients apply with abdominal swelling, constipation, severe abdominal pain in the form of recurrent cramps and vomiting. In direct abdominal radiographs, dilated small intestines, air-fluid levels or foamy appearances are observed in the ileocecal region. Obstruction developed in patients with cystic fibrosis is treated with medical and surgical methods with a multidisciplinary approach depending on the degree of severity and symptoms. In this paper, two critically ill children with cystic fibrosis were presented who were followed up in the pediatric intensive care unit with a diagnosis of DIOS, with one treated conservatively and the other surgically; the treatment methods were also highlighted.